Two centuries of solidarity : German, Belgian and Dutch social health insurance 1770-2008 - Companje, Karel-Peter; Hendriks, R.H.M.; Veraghtert, Karel; Widdershoven, Brigitte (Amsterdam: Aksant, 2009)
"K.P. Companje, R.H.M. Hendriks, K.F.E. Veraghtert and B.E.M. Widdershoven"